Splicing and expression dynamics of SR genes in hot pepper (Capsicum annuum): regulatory diversity and conservation under stress - Li, Lin; Zhang, Yueqin; Zhang, Rui; Cen, Xiangtao; Huang, Yongxiang; Hu, Hanqiao; Jiang, Xingyu; Ling, Yu (Frontiers in Plant Science, 2025)
In this study, we identified and characterized 23 genes encoding serine/arginine-rich (SR) protein in hot pepper (Capsicum annuum), named CaSR here. These CaSR proteins are grouped into seven subfamilies. Phylogenetic analysis revealed a high degree of similarity between CaSRs and their homologous proteins in other plants. Promoter regions of SR proteins are enriched with elements relating to light response, stress, hormone signaling, and plant growth. Notably, transcription levels of several proteins, including CaSR33, CaSR34, and CaSR34a, were upregulated by salt, drought, and cold stresses, suggesting potential roles of these proteins in stress tolerance. We also observed an increase of CaSR transcript population resulting from alternative splicing (AS) regulation, mainly intron retention. AS patterns of CaSR genes varied among tissues. Higher AS intensity was found in the RS subfamily, while some genes in the RSZ subfamily showed no AS regulation under the conditions used here. Interestingly, a cross-species comparative study with Arabidopsis (Arabidopsis thaliana) and tomato (Solanum lycopersicum) showed that many AS events impact the region which codes the RNA recognition motif (RRM) domain of the protein, indicating a conserved regulatory mechanism of SR proteins in plants. Our findings reveal the functional diversity and evolutionary conservation of SR proteins in hot pepper and highlight AS as a mechanism enhancing plant adaptability, providing insights for future stress-resistant crop development.